Integrated method management 'ilman wa ruuhan at madrasah ibtidaiyah terpadu (mit) as salam ambon - M Sahrawi Saimima; Thati Kaplale (12 Waiheru, 2023)
Current learning methods, experiencing significant development. In terms of management, there are those who provide convenience to teachers, there are also teachers who need training to understand them. Like metode terpadu ’ilman wa ruuhan. Since the introduction of this method at MIT As Salam Ambon in 2020, this method is considered to still require adjustment by some teachers. This research was carried out with the aim of knowing how the integrated management method ‘ilman wa ruuhan at MIT As Salam Ambon. Then what advantages and disadvantages are experienced when this method is applied. This paper uses qualitative research as a process in answering these two questions. The subjects of this study are teaching staff (ustazah) in classes I and II. The results showed that the integrated management method ‘ilman wa ruuhan was carried out in two stages, namely time management and setting the rhythm of reading. In time management for the application of the integrated method ‘ilman wa ruuhan, the ustazah at MIT As Salam Ambon set aside 1 hour to teach this method. During the 60 minutes, the process starts from the opening stage with a duration of 5 minutes, memorization of 15 minutes, core activities of 35 minutes and closing of 5 minutes. Meanwhile, for rhythm setting, it takes the expertise of the ustazah to practice it to students. Then for the advantages of this method has been equipped with a guidebook, which can be used by the ustazah to apply it to the students. For its own shortcomings, perhaps the fundamental factor is that the method is relatively new, and requires adjustment from the teachers.